Tillage Method and Residual N, P, K, Zn, B, Mg, Ca, and S Nutrients Effect on Growth and Yield of Dry Bean Grown after the Harvest of Maize - Hillary Moses Omondi Otieno; George N. Chemining’wa; Shamie Zingore; Charles K. Gachene (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Common bean (Phaseolus vulgaris L.) production is constrained majorly by drought and low soil fertility in Kenya. These limitations have never been adequately approached due to financial challenges and lack of better technology. A study was carried out in Kirinyaga and Embu Counties to evaluate the effects of tillage method and residual fertilizers on yield performance of dry bean. Dry bean was grown in the short rains season on plots preceded by fertilized maize (Zea mays L.) grown in the long rains season. The trials were laid out in a randomized complete block design with a split-plot arrangement. The tillage methods, NT+CR and CT-CR, where NT: No-tillage, CT: Conventional tillage, and CR: Crop residue, were assigned the main plot and residual fertilizers (NK, NP, PK, NPK, and NPK+CaMgZnBS) the subplots. The results showed that there was 35% and 46% more water retention under NT+CR than under CT-CR system in Embu and Kirinyaga sites, respectively. NT+CR produced higher biomass, more number of pods per plant, number of seeds per pod, and 1000-seed weight. Plots with residual NPK+ZnBMgCaS yielded higher biomass at 60 DAE, number of seeds per pod, 1000-seed weight and grain yield than plots with other treatments. The residual NPK+ZnBMgCaS and NPK treatments out yielded PK treatment by 600 kg ha-1 and 370 kg ha-1 (Embu) and by 710 kg ha-1 and 330 kg ha-1 (Kirinyaga), respectively. Based on these results, cultivation of dry bean on residual fertilizer nutrients solely or in combination with no-till and crop residue retention after maize harvest has the potential to improve the yields and food security among farmers in the region.